Indigenous partnership for agrobiodiversity and food sovereignty - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The partnership’s mission is to improve ways of linking indigenous peoples and local communities interested in pursuing self-determined development and to facilitate such communities in taking a leadership role in agrobiodiversity dialogues. It aims to advocate and strengthen the voice of indigenous groups at policy level and promote their unique wisdom.